PENGARUH ANALISIS PROSPEKTUS DAN MANAJEMEN LABA TERHADAP INITIAL RETURN DI BURSA EFEK INDONESIA - Lestari, Yona Octiani (Fakultas Ekonomi, UIN Maliki Malang, 2010)
Research target is test prospectus information influence to initial return. Sample Research as much 53 manufacturing and non manufacturingÂ doing tender in JSX (Jakarta Stock Exchange) at range of time 2005-2007. Intake sample method by purposive sampling with equity criterion which underpricing prospectus report and published fulfill data equipment. Analyse data use doubled regression to testÂ strength of among auditor reputation, emission guarantor reputation, old age company, equity percentage which on the market, ROA, leverage, industrial sector of earning management with initial return. Result of analysis indicate that there is two variable having an effect on significance to initial return that is emission guarantor reputation and auditor reputation. Assess significance T for the auditor reputation is 0.037 meaning significance atÂ 5%. While result of test correlation indicate that emission guarantor reputation variable can explain initial return equal to 0.200 or equal to 20% positive to initial return. This result support research which have been done by Balvers ( 1998) that is emission guarantor reputation and auditor reputation have an effect on negativity significance to initial return.